Technological Frontier and Sectoral Technical Efficiency in Mexico: A Data Envelopment Analysis - Becerril-Torres, Osvaldo (2012)
This research aims to determine Mexico’s technological frontier and sectoral technical efficiency. The methodology employed is Data Envelopment Analysis. The results show, first, that sectors related to agriculture, mining, manufacturing, financial services, and professional and corporate services are fully efficient under variable returns to scale, whereas under constant returns to scale sector 11 is excluded; the average efficiency is 0.71 under variable returns to scale and 0.64 under constant returns to scale, indicating that there is potential to improve output by approximately 30% through better use of capital and labor.